Mothers' Experiences with Antenatal Milk Expression. Issue 5 (September 2021) - Juntereal, Nina A.; Spatz, Diane L.
Abstract: Background: Antenatal milk expression is a milk expression intervention beginning at either 36 or 37 weeks of gestation for the purpose of potential colostrum collection and storage prior to birth for postnatal infant feeding. Research on antenatal milk expression is limited and originates outside the United States. Methods: Women who used antenatal milk expression were interviewed about their experiences. A conventional, inductive approach to qualitative content analysis was used to analyze participants' responses. Results: Three women participated in interviews. They reported learning and performing antenatal milk expression for various postpartum needs including avoidance of formula, milk available for potential infant hypoglycemia, and to support human milk feeding during surrogate mother–infant separation. These mothers obtained education and information on antenatal milk expression primarily on their own. Clinical Implications: Greater awareness and understanding of antenatal milk expression is needed in the professional community caring for childbearing women. Perinatal nurses need to be aware of all breastfeeding practices including antenatal milk expression. Knowledge of the practice and advocacy for more research on antenatal milk expression will improve lactation support and ensure expectant mothers reach their personal breastfeeding goals. Abstract : Antenatal milk expression may be a way to avoid formula supplementation for infants with hypoglycemia after birth, but more data are needed on efficacy, safety, and outcomes for mothers and babies. In this study women who practiced antenatal milk expression share their rationale and experiences.